Analisis Minat Siswa dalam Mengikuti Ekstrakurikuler Futsal (Survei pada Siswa SMA NEGERI 1 POLANHARJO) - Wijayanto, Ismail; Nugroho, Hanif; Warthadi, Anugrah Nur; Fatoni, Muhad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to analyze student interest in participating in extracurricular futsal at SMA Negeri 1 Polanharjo and identify the factors that influence it. This research uses a quantitative descriptive method. The population in this research is all SMA Negeri 1 Polanharjo students, totaling 379 students, while the sample taken was 26 students who took part in extracurricular futsal at the school. Sampling was carried out using a purposive sampling technique with specific criteria, namely active students at SMA Negeri 1 Polanharjo who were involved in futsal extracurriculars and were ready to participate in a research series. Using quantitative descriptive methods, the results show high student interest, reaching 77.62%. Conclusion: This research shows that students' interest in participating in extracurricular futsal at SMA Negeri 1 Polanharjo is relatively high, with a percentage reaching 77.62%. Even though these results are considered good, ongoing support and outreach are still needed from various parties, such as the school, environment, family, and teachers or trainers. Keywords: Extracurricular, Futsal, Interests, Students,